PENYERAPAN LOGAM BERAT (Pb) OLEH LIMBAH KULIT JENGKOL (Pithecellobium jiinga) - Merry Thressia (EcoNews, 2020)
Heavy metals in aquatic environments have been known to cause some damage to aquatic life. Pb metal is found in waste that pollute the waters. In modern life today many people have a habit of disposing of garbage disembarang place. Utilization of jengkol skin powder which is organic waste scattered in the traditional market can be used for the processing of liquid waste containing Pb metal. This research used experimental method by using Atomic Absorption Spectrophotometer which then analyzed statistically using two way ANOVA test without interaction. From the results of the study found that jengkol skin powder can absorb Pb metal that exists in the liquid waste in the surrounding environment. After statistical test with two- way ANOVA test without interaction, Pb metal absorption by jengkol skin powder with pH and mass ratio, then got value of F count (mass) = 3,763 and F value table = 98,50 while F value count (pH) = 0,812 with value F table = 99,00 with result Ha rejected and H0 accepted. From the results of this study can be concluded that there is no significant difference in the absorption of Pb logan using jengkol skin powder in pH and mass variations.